Microbial Quality and Production Methods of Traditional Fermented Cheeses in Lebanon - Mabelle Chedid; Houssam Shaib; Lina Jaber; Youmna El Iskandarani; Shady Kamal Hamadeh (International Journal of Food Science)
This study is aimed at evaluating the quality and safety of two traditional fermented dairy products commonly found in Lebanon (Ambarees and Kishk in its dry and wet forms) by detecting foodborne pathogens and indicator microorganisms. Additionally, it seeks to identify the strengths, weaknesses, opportunities, and threats to quality and the production level. A total of 58 random samples (duplicated) including goat milk (n=16), dry Kishk (n=8), wet Kishk (n=8), and Ambarees (n=26) were collected from individuals who both farm and process these products. They represent the two production levels within the identified value chains in the Shouf and West Bekaa regions. Microbiological analyses revealed that all samples were free of Escherichia coli, while Staphylococcus aureus was found in all of them with significantly higher levels of contamination in wet Kishk, indicating poor hygienic practices at the different production levels. Coliforms were found in only 3.8% of the Ambarees samples, made from raw milk, showing that the decreasing pH and water activity throughout the long milk fermentation process contributes to the low prevalence of these microorganisms and that cross-contamination might have occurred during the packaging phase. A regional pattern was observed where microbial counts (total aerobic counts, total coliforms, and S. aureus) were found significantly higher (p<0.05) in milk samples of the West Bekaa, suggesting better hygienic conditions in the Shouf as compared to the West Bekaa. This analysis would be an important tool for developing the goat dairy sector and enhancing the production and promotion of traditional goat milk products. Valorization at the different levels of the value chain, starting with the adoption of good production practices on the farm, training on hygienic standards, innovation in packaging and marketing, and developing adequate policies, may ensure high-quality end-products that will eventually contribute to the livelihoods of the main stakeholders in this value chain and help preserve these national culinary gems.